2007
DOI: 10.1002/cbic.200700160
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Universal 5‐Nitroindole Ribonucleotide and Incorporation into RNA by a Viral RNA‐Dependent RNA Polymerase

Abstract: Small molecules that mimic natural nucleosides and nucleotides comprise a major class of antiviral agents. A new approach to the design of these compounds focuses on the generation of lethal mutagens: [1,2] compounds that further accelerate the high rate of viral mutagenesis [3,4] to confer antiviral effects. By incorporating artificial nucleobases with degenerate base-pairing abilities into viral genomes, lethal mutagens increase viral genomic mutagenesis to intolerable levels during replication, a process te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Despite this, previous attempts to design novel mutagenic nucleotide analogues that are capable of inducing mutation in RNA viruses have had only limited success (17)(18)(19)39). In this study, we have demonstrated that rPTP is an efficient and ambiguous substrate of a viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite this, previous attempts to design novel mutagenic nucleotide analogues that are capable of inducing mutation in RNA viruses have had only limited success (17)(18)(19)39). In this study, we have demonstrated that rPTP is an efficient and ambiguous substrate of a viral RNA-dependent RNA polymerase.…”
Section: Discussionmentioning
confidence: 74%
“…We have previously investigated the use of "universal" bases with minimal hydrogen bonding potential as lethal mutagens of PV (17,19). Here we investigate the antiviral and mutagenic potential of a nucleoside analogue with the capacity to stably base pair with two natural nucleobases.…”
mentioning
confidence: 99%
“…The antiviral activity of 5-nitrocytidine was first described against poliovirus and coxsackievirus B3, demonstrating greater inhibition potency than the control drug ribavirin (Harki et al, 2007). In the same study, 5-nitrocytidine triphosphate (NCT) inhibited poliovirus RdRp activity.…”
Section: -Nitro and 2 -Amino Cytidinementioning
confidence: 99%
“…Mutagenesis can provide an advantage over conventional non-mutagenic inhibitors because mutagenized genomes may suppress the most infective subpopulations of genomes coexisting in the same quasispecies, as discussed in the next section. A number of base and nucleoside analogues are currently under development as potential new antiviral mutagenic agents [44,45,46,47,48,49,50]. …”
Section: Contributions Of Lcmv To Lethal Mutagenesismentioning
confidence: 99%